Low-alkali anti-freezing Portland cement for plateau regions and preparation method thereof

High-strength, crack resistance and frost resistance low alkali and frost resistance silicate cement was prepared by sulfide-degraded glycidyl ether and amino-polyethylene glycol-maleimide. The expansion stress and crack problems of cement in harsh climates in plateau areas have been solved, and the overall performance of concrete has been improved.

CN119118543AActive Publication Date: 2024-12-13TIBET GAOZHENG CONSTR MATERIAL CO LTD
View PDF 3 Cites 0 Cited by

Patent Information

Application Number
CN202411268479.7
Authority / Receiving Office
CN · China
Patent Type
Applications(China)
Current Assignee / Owner
Filing Date
2024-09-11
Publication Date
2024-12-13
Estimated Expiration
2044-09-11

AI Technical Summary

Technical Problem

In plateau areas, the high alkalinity of ordinary silicate cement leads to concrete expansion stress and crack problems. The existing low-alkali cement has reduced crack resistance and frost resistance after improving early strength and corrosion resistance, making it difficult to meet the harsh climate conditions. Highway construction demand.

Method used

Using sulfide glycidyl ether and amino-polyethylene glycol-maleimide as modified aids, low-alkali anti-freeze silicate cement is prepared through click chemical reaction and epoxy-amino cross-linking, and combined with Fly ash and gypsum are ball milled to form low-alkali cement with high strength, crack resistance and frost resistance.

Benefits of technology

It improves the early strength, crack resistance and frost resistance of concrete, is suitable for applications in harsh climatic conditions in plateau areas, and reduces the expansion stress and crack risks of concrete.

✦ Generated by Eureka AI based on patent content.
Patent Text Reader

Abstract

The invention relates to low-alkali anti-freezing Portland cement for plateau regions and a preparation method thereof, the preparation method comprises the following steps: step 1, weighing allyl alcohol glycidyl ether, adding the allyl alcohol glycidyl ether into absolute ethyl alcohol, adding 2, 3-dimercaptopropanol, adding a photoinitiator, and reacting under the action of ultraviolet light to obtain thioetherified glycidyl ether; 2, thioetherified glycidyl ether and amino-polyethylene glycol-maleimide are mixed in absolute ethyl alcohol, the mixture is heated and stirred for a reaction, and a modified grinding aid is obtained; and step 3, adding the low-alkali cement clinker, fly ash, gypsum and the modified grinding aid into a ball mill, carrying out grinding treatment, and after grinding is finished, sieving to obtain the low-alkali anti-freezing Portland cement. The Portland cement prepared by the invention is prepared by mixing and grinding the low-alkali cement clinker, the fly ash and the gypsum by using the modified grinding aid. Experimental application shows that the low-alkali cement prepared by the invention has relatively high strength, crack resistance and freezing resistance.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to the field of building materials, and in particular to a low-alkali antifreeze silicate cement for plateau areas and a preparation method thereof. Background Art

[0002] General Portland cement is a hydraulic cementitious material made of Portland cement clinker, an appropriate amount of gypsum and specified mixed materials; the mixed materials include granulated blast furnace slag, granulated blast furnace slag powder, fly ash, and pozzolanic cement. General Portland cement is divided into Portland cement, ordinary Portland cement, slag Portland cement, pozzolanic Portland cement, fly ash Portland cement and composite Portland cement according to the type and dosage of mixed materials. These different types of cement have different chemical and physical properties. In various projects, suitable cement should be selected according to the project characteristics, use requirements and the characteristics of various cements.

[0003] In the western plateau area of ​​my country, the climatic conditions are very harsh, the terrain, landform and hydrogeological conditions are complex, and the fragile ecological environment has brought great challenges to highway construction. The high-quality raw materials that can be used to build asphalt pavements are relatively scarce, which has brought great constraints to local highway construction. Ordinary Portland cement has a high alkali content. After construction, the alkali in the cement will react with certain components in the aggregate in the concrete to generate silicate gel, which is easy to cause the concrete volume to increase and produce expansion stress. In severe cases, it will also cause cracks in the concrete, causing safety hazards in the project. In order to avoid the emergence of such safety hazards, the existing technology will use a large amount of low-alkali cement to reduce cracks in the concrete body. Although the low-alkali Portland cement on the market can improve the early strength and corrosion resistance of concrete, the addition of alkali activators greatly increases the alkalinity of cement, and it is no longer able to have good crack resistance and frost resistance, and the strength in the later period is also significantly reduced. Summary of the invention

[0004] In view of the problems existing in the prior art, the object of the present invention is to provide a low-alkali antifreeze silicate cement for use in plateau areas and a preparation method thereof.

[0005] The purpose of the present invention is achieved by adopting the following technical solutions:

[0006] In a first aspect, the present invention provides a method for preparing low-alkali antifreeze silicate cement for plateau areas, comprising the following steps:

[0007] Step 1, weigh allyl alcohol glycidyl ether and add it into anhydrous ethanol, after fully dissolving, add 2,3-dimercaptopropanol, stir well again, add photoinitiator under the condition of nitrogen as protective gas, stir and react for 1-2h under the action of ultraviolet light, after the reaction is completed, remove the solvent under reduced pressure to obtain thioetherified glycidyl ether;

[0008] Step 2, mixing thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL) in anhydrous ethanol, stirring well, heating to reflux, stirring to react for 2-5 hours, and after the reaction is completed, removing the solvent by reduced pressure distillation to obtain a modified grinding aid;

[0009] Step 3, adding low-alkali cement clinker, fly ash, gypsum and modified grinding aid into a ball mill for grinding. After the grinding is completed, the low-alkali antifreeze silicate cement is obtained by sieving.

[0010] Preferably, in step 1, the mass ratio of allyl alcohol glycidyl ether, 2,3-dimercaptopropanol and anhydrous ethanol is 1.4-2.8:0.6-1.2:40-60.

[0011] Preferably, in step 1, the photoinitiator is one of benzoin dimethyl ether, benzoin ethyl ether and benzoin butyl ether, and the amount of the photoinitiator added is 1.5%-5.5% of the mass of allyl alcohol glycidyl ether.

[0012] Preferably, in step 1, the power of the ultraviolet light is 50-100 W and the wavelength is 365 nm.

[0013] Preferably, in step 2, the mass ratio of thioetherified glycidyl ether, amino-polyethylene glycol-maleimide (NH2-PEG-MAL) and anhydrous ethanol is 0.21-0.42:0.8-1.6:10-20.

[0014] Preferably, in step 2, the weight average molecular weight (Mw) of epoxy-polyethylene glycol-acrylamide (EPO-PEG-ACA) is 500-2000.

[0015] Preferably, in step 2, the temperature of the heating reflux is 65-75°C.

[0016] Preferably, in step 3, the rotation speed of the ball mill is 40-80 r / min, and the grinding time is 20-40 min.

[0017] Preferably, in step 3, the sieve residue rate of the low-alkali antifreeze silicate cement on a 45 μm square hole sieve after sieving is less than 5%.

[0018] Preferably, in step 3, the mass ratio of low-alkali cement clinker, fly ash, gypsum and modified grinding aid is 100:6-10:6-12:0.1-0.5.

[0019] Preferably, in step 3, the components of the low-alkali cement clinker, calculated by weight percentage, include: SiO2: 22.67%, CaO: 64.56%, Al2O3: 5.25%, Fe2O3: 3.65%, MgO: 1.59%, K2O: 0.32%, Na2O: 0.22%, SO3: 0.33% and other impurities.

[0020] Preferably, in step 3, the components of the gypsum, calculated by weight percentage, include: CaO: 32.32%, SiO2: 0.86%, Al2O3: 0.32%, MgO: 2.07%, SO3: 42.34%, H2O: 18.24% and other impurities.

[0021] Preferably, in step 3, the fly ash is class I fly ash or class II fly ash.

[0022] In a second aspect, the present invention provides a low-alkali antifreeze silicate cement for use in plateau areas, which is prepared by the above-mentioned preparation method.

[0023] In a third aspect, the present invention provides an application of low-alkali antifreeze silicate cement in concrete for plateau areas, wherein the concrete, calculated by weight, comprises:

[0024] 100 parts of low-alkali frost-resistant silicate cement, 313-354 parts of coarse aggregate, 472-526 parts of fine aggregate, 55-75 parts of fly ash, 28-56 parts of polyester fiber, 1.3-2.6 parts of high-efficiency water reducer and 78-96 parts of water.

[0025] Preferably, the coarse aggregate is crushed stone or pebbles with a particle size between 5-10 mm, and the fine aggregate is river sand or sea sand with a particle size between 0.16-4.5 mm.

[0026] Preferably, the fly ash is Class I fly ash.

[0027] Preferably, the polyester fiber has a length of 5-8 mm and a diameter of 20±2 μm.

[0028] Preferably, the polyester fiber is at least one of polybutylene terephthalate fiber (PBT fiber), polyhexamethylene terephthalate fiber (PET fiber), and polytrimethylene terephthalate fiber (PTT fiber).

[0029] Preferably, the high-efficiency water reducer is TH-928 polycarboxylic acid-based high-performance water reducer.

[0030] The beneficial effects of the present invention are:

[0031] 1. The present invention prepares a low-alkali antifreeze silicate cement for plateau areas. The silicate cement is low-alkali cement, which is prepared by mixing and grinding low-alkali cement clinker, fly ash and gypsum with a modified grinding aid. Experimental application shows that the low-alkali cement prepared by the present invention has high strength, crack resistance and frost resistance.

[0032] 2. In the preparation of low-alkali cement, the grinding aid used in the present invention is prepared by cross-linking epoxy-amino groups of thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL), and the thioetherified glycidyl ether is prepared by a thiol-double bond click chemistry reaction using allyl alcohol glycidyl ether and 2,3-dimercaptopropanol as reactants. Compared with traditional alcohol amine grinding aids, the grinding aid prepared by the present invention can not only ensure grinding aid, but also improve the strength, crack resistance and frost resistance of concrete. DETAILED DESCRIPTION

[0033] The technical solution of the present invention is described below through specific examples. It should be understood that the one or more method steps mentioned in the present invention do not exclude the existence of other method steps before and after the combination step or the insertion of other method steps between these explicitly mentioned steps; it should also be understood that these embodiments are only used to illustrate the present invention and are not used to limit the scope of the present invention. Moreover, unless otherwise specified, the numbering of each method step is only a convenient tool for identifying each method step, and is not intended to limit the order of arrangement of each method step or to limit the scope of the present invention. The change or adjustment of the relative relationship thereof shall also be regarded as the scope of the present invention without substantially changing the technical content.

[0034] In order to better understand the above technical scheme, the exemplary embodiments of the present invention are described in more detail below. Although exemplary embodiments of the present invention are shown, it should be understood that the present invention can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided in order to enable a more thorough understanding of the present invention and to enable the scope of the present invention to be fully communicated to those skilled in the art.

[0035] The components of the low-alkali cement clinker used in the embodiment of the present invention are calculated by weight percentage and include: SiO2: 22.67%, CaO: 64.56%, Al2O3: 5.25%, Fe2O3: 3.65%, MgO: 1.59%, K2O: 0.32%, Na2O: 0.22%, SO3: 0.33% and other impurities.

[0036] The components of the gypsum used in the embodiment of the present invention are calculated by weight percentage and include: CaO: 32.32%, SiO2: 0.86%, Al2O3: 0.32%, MgO: 2.07%, SO3: 42.34%, H2O: 18.24% and other impurities.

[0037] The present invention will be further described below in conjunction with the following examples.

[0038] Example 1

[0039] A method for preparing low-alkali antifreeze silicate cement for plateau areas comprises the following steps:

[0040] Step 1, weighing allyl alcohol glycidyl ether and adding it to anhydrous ethanol, after fully dissolving, adding 2,3-dimercaptopropanol, the mass ratio of allyl alcohol glycidyl ether, 2,3-dimercaptopropanol and anhydrous ethanol is 2.1:0.9:50, stirring again, adding benzoin dimethyl ether under the condition of nitrogen as protective gas, the addition amount is 3.5% of the mass of allyl alcohol glycidyl ether, stirring and reacting for 1.5h under the action of ultraviolet light, the power of ultraviolet light is 80W, and the wavelength is 365nm. After the reaction is completed, the solvent is removed under reduced pressure to obtain thioetherified glycidyl ether;

[0041] Step 2, mixing thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL, Mw=1000) in anhydrous ethanol, the mass ratio of thioetherified glycidyl ether, amino-polyethylene glycol-maleimide (NH2-PEG-MAL) and anhydrous ethanol being 0.31:1.2:15, stirring well, heating to reflux at 70°C, stirring to react for 2-5h, and after the reaction is completed, removing the solvent by reduced pressure distillation to obtain a modified grinding aid;

[0042] Step 3, adding low-alkali cement clinker, Class I fly ash, gypsum and modified grinding aid into a ball mill, wherein the mass ratio of low-alkali cement clinker, fly ash, gypsum and modified grinding aid is 100:9:8:0.3, the rotation speed of the ball mill is 60r / min, the grinding time is 30min, and grinding treatment is performed. After the grinding is completed, sieving is performed, and the sieve residue rate on the 45μm square hole sieve is less than 5%, thereby obtaining low-alkali antifreeze silicate cement.

[0043] The above-mentioned application of low-alkali antifreeze silicate cement in concrete for plateau areas, calculated by weight, includes:

[0044] 100 parts of low-alkali frost-resistant silicate cement, 327 parts of coarse aggregate, 508 parts of fine aggregate, 65 parts of fly ash, 42 parts of polyester fiber, 2.1 parts of high-efficiency water reducer and 87 parts of water.

[0045] Among them, coarse aggregate is crushed stone or pebbles with a particle size between 5-10mm; fine aggregate is river sand or sea sand with a particle size between 0.16-4.5mm; fly ash is Class I fly ash; polyester fiber is PBT fiber with a length of 5-8mm and a diameter of 20±2μm; and high-efficiency water reducer is TH-928 polycarboxylic acid-based high-performance water reducer.

[0046] Example 2

[0047] A method for preparing low-alkali antifreeze silicate cement for plateau areas comprises the following steps:

[0048] Step 1, weighing allyl alcohol glycidyl ether and adding it to anhydrous ethanol, after fully dissolving, adding 2,3-dimercaptopropanol, the mass ratio of allyl alcohol glycidyl ether, 2,3-dimercaptopropanol and anhydrous ethanol is 1.4:0.6:40, stirring again, adding benzoin ethyl ether under the condition of nitrogen as protective gas, the addition amount is 1.5% of the mass of allyl alcohol glycidyl ether, stirring and reacting for 1h under the action of ultraviolet light, the power of ultraviolet light is 50W, and the wavelength is 365nm. After the reaction is completed, the solvent is removed under reduced pressure to obtain thioetherified glycidyl ether;

[0049] Step 2, mixing thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL, Mw=500) in anhydrous ethanol, the mass ratio of thioetherified glycidyl ether, amino-polyethylene glycol-maleimide (NH2-PEG-MAL) and anhydrous ethanol being 0.21:0.8:10, stirring well, heating to reflux at 65°C, stirring to react for 2h, and after the reaction is completed, removing the solvent by reduced pressure distillation to obtain a modified grinding aid;

[0050] Step 3, adding low-alkali cement clinker, grade II fly ash, gypsum and modified grinding aid into a ball mill, the mass ratio of low-alkali cement clinker, fly ash, gypsum and modified grinding aid is 100:6:6:0.1, the speed of the ball mill is 40r / min, the grinding time is 20min, and the grinding treatment is carried out. After the grinding is completed, sieving is performed, and the sieve residue rate on the 45μm square hole sieve is less than 5%, thereby obtaining low-alkali antifreeze silicate cement.

[0051] The above-mentioned application of low-alkali antifreeze silicate cement in concrete for plateau areas, calculated by weight, includes:

[0052] 100 parts of low-alkali frost-resistant silicate cement, 313 parts of coarse aggregate, 472 parts of fine aggregate, 55 parts of fly ash, 28 parts of polyester fiber, 1.3 parts of high-efficiency water reducer and 78 parts of water.

[0053] Among them, the coarse aggregate is crushed stone or pebbles with a particle size between 5-10mm; the fine aggregate is river sand or sea sand with a particle size between 0.16-4.5mm; the fly ash is Class I fly ash; the polyester fiber is PET fiber with a length of 5-8mm and a diameter of 20±2μm; and the high-efficiency water reducer is TH-928 polycarboxylic acid-based high-performance water reducer.

[0054] Example 3

[0055] A method for preparing low-alkali antifreeze silicate cement for plateau areas comprises the following steps:

[0056] Step 1, weighing allyl alcohol glycidyl ether and adding it to anhydrous ethanol, after fully dissolving, adding 2,3-dimercaptopropanol, the mass ratio of allyl alcohol glycidyl ether, 2,3-dimercaptopropanol and anhydrous ethanol is 2.8:1.2:60, stirring again, adding benzoin butyl ether under the condition of nitrogen as protective gas, the addition amount is 5.5% of the mass of allyl alcohol glycidyl ether, stirring and reacting for 2h under the action of ultraviolet light, the power of ultraviolet light is 100W, and the wavelength is 365nm. After the reaction is completed, the solvent is removed under reduced pressure to obtain thioetherified glycidyl ether;

[0057] Step 2, mixing thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL, Mw=2000) in anhydrous ethanol, the mass ratio of thioetherified glycidyl ether, amino-polyethylene glycol-maleimide (NH2-PEG-MAL) and anhydrous ethanol being 0.42:1.6:20, stirring well, heating to reflux at 75°C, stirring for reaction for 5h, and after completion of the reaction, removing the solvent by reduced pressure distillation to obtain a modified grinding aid;

[0058] Step 3, adding low-alkali cement clinker, Class I fly ash, gypsum and modified grinding aid into a ball mill, wherein the mass ratio of low-alkali cement clinker, fly ash, gypsum and modified grinding aid is 100:10:12:0.5, the rotation speed of the ball mill is 80r / min, the grinding time is 40min, and grinding treatment is performed. After the grinding is completed, sieving is performed, and the sieve residue rate on the 45μm square hole sieve is less than 5%, thereby obtaining low-alkali antifreeze silicate cement.

[0059] The above-mentioned application of low-alkali antifreeze silicate cement in concrete for plateau areas, calculated by weight, includes:

[0060] 100 parts of low-alkali frost-resistant silicate cement, 354 parts of coarse aggregate, 526 parts of fine aggregate, 75 parts of fly ash, 56 parts of polyester fiber, 2.6 parts of high-efficiency water reducer and 96 parts of water.

[0061] Among them, the coarse aggregate is crushed stone or pebbles with a particle size between 5-10mm; the fine aggregate is river sand or sea sand with a particle size between 0.16-4.5mm; the fly ash is Class I fly ash; the polyester fiber is PTT fiber with a length of 5-8mm and a diameter of 20±2μm; and the high-efficiency water reducer is TH-928 polycarboxylic acid-based high-performance water reducer.

[0062] Comparative Example 1

[0063] A low-alkali silicate cement, which is different from the preparation method of Example 1 in that the modified grinding aid is replaced by triethanolamine (traditional small molecule alcohol amine), and the rest is the same as Example 1.

[0064] Comparative Example 2

[0065] A low-alkali silicate cement, which is different from the preparation method of Example 1 in that the modified grinding aid is replaced by allyl alcohol glycidyl ether, and the rest is the same as Example 1.

[0066] Comparative Example 3

[0067] A low-alkali silicate cement, which is different from the preparation method of Example 1 in that the modified grinding aid is replaced by amino-polyethylene glycol-maleimide (NH2-PEG-MAL, Mw=1000), and the rest is the same as Example 1.

[0068] Experimental testing

[0069] The low-alkali cement prepared in Example 1 of the present invention and Comparative Examples 1-3 were respectively used in concrete according to the method of Example 1, mixed in a mold and formed, and then the performance of the concrete was tested after curing for 28 days.

[0070] The test standards include:

[0071] (1) Compressive strength: GB / T 50081-2016, testing includes 7d and 28d strength;

[0072] (2) Crack resistance (crack resistance grade): JGJ / T 193-2009, the grades are divided into LI, L-II, L-III, L-IV, and LV. The higher the grade, the better the crack resistance.

[0073] (3) Antifreeze property (quick freezing method, antifreeze grade): GB / T 50164-2009, antifreeze grades are divided into nine grades: F50, F100, F150, F200, F250, F300, F350, F400, and >F400. The higher the grade, the better the antifreeze property.

[0074] The experimental test results are shown in Table 1.

[0075] Table 1 Performance of different concrete

[0076] Example 1 Comparative Example 1 Comparative Example 2 Comparative Example 3 7d compressive strength (MPa) 41.3 36.8 34.4 38.5 28d compressive strength (MPa) 53.4 47.1 45.2 50.6 Crack resistance grade LV L-III L-Ⅱ L-III Frost resistance level F400 F250 F200 F300

[0077] From the results in Table 1, it can be seen that the 7-day and 28-day compressive strengths of the concrete prepared using the cement of Example 1 of the present invention are higher than those of the comparative example, indicating that its strength performance is better. In addition, the crack resistance and frost resistance grades of Example 1 are also much better than those of the comparative example, indicating that the concrete prepared using the cement of Example 1 of the present invention has excellent crack resistance and frost resistance on the basis of high strength, and is more suitable for use in plateau areas with high altitude and low temperature.

[0078] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representation of the above terms should not be understood as necessarily being directed to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine different embodiments or examples described in this specification.

[0079] Although the embodiments of the present invention have been shown and described above, it is to be understood that the above embodiments are exemplary and are not to be construed as limitations of the present invention. A person skilled in the art may change, modify, replace and vary the above embodiments within the scope of the present invention.

Claims

1. A method for preparing low-alkali antifreeze silicate cement for plateau areas, characterized in that: The following steps are involved: Step 1, weigh allyl alcohol glycidyl ether and add it into anhydrous ethanol, after fully dissolving, add 2,3-dimercaptopropanol, stir well again, add photoinitiator under the condition of nitrogen as protective gas, stir and react for 1-2h under the action of ultraviolet light, after the reaction is completed, remove the solvent under reduced pressure to obtain thioetherified glycidyl ether; Step 2, mixing thioetherified glycidyl ether and amino-polyethylene glycol-maleimide (NH2-PEG-MAL) in anhydrous ethanol, stirring well, heating to reflux, stirring to react for 2-5 hours, and after the reaction is completed, removing the solvent by reduced pressure distillation to obtain a modified grinding aid; Step 3, adding low-alkali cement clinker, fly ash, gypsum and modified grinding aid into a ball mill for grinding. After the grinding, the low-alkali antifreeze silicate cement is sieved to obtain the low-alkali antifreeze silicate cement.

2. The method for preparing low-alkali antifreeze silicate cement for plateau areas according to claim 1, characterized in that: In the step 1, the mass ratio of allyl alcohol glycidyl ether, 2,3-dimercaptopropanol and anhydrous ethanol is 1.4-2.8:0.6-1.2:40-60.

3. The method for preparing low-alkali antifreeze silicate cement for plateau areas according to claim 1, characterized in that: In the step 1, the photoinitiator is one of benzoin dimethyl ether, benzoin ethyl ether and benzoin butyl ether, and the amount of the photoinitiator added is 1.5%-5.5% of the mass of allyl alcohol glycidyl ether.

4. The method for preparing low-alkali antifreeze silicate cement for plateau areas according to claim 1, characterized in that: In the step 2, the mass ratio of thioetherified glycidyl ether, amino-polyethylene glycol-maleimide and anhydrous ethanol is 0.21-0.42:0.8-1.6:10-20; and the weight average molecular weight of epoxy-polyethylene glycol-acrylamide is 500-2000.

5. The method for preparing low-alkali antifreeze silicate cement for plateau areas according to claim 1, characterized in that: In the step 3, the rotation speed of the ball mill is 40-80 r / min, and the grinding time is 20-40 min; after sieving, the sieve residue rate of the low-alkali antifreeze silicate cement on the 45 μm square hole sieve is less than 5%.

6. The method for preparing low-alkali antifreeze silicate cement for plateau areas according to claim 1, characterized in that: In step 3, the mass ratio of low-alkali cement clinker, fly ash, gypsum and modified grinding aid is 100:6-10:6-12:0.1-0.

5.

7. A low-alkali antifreeze silicate cement for use in plateau areas, characterized in that: The preparation method according to claim 1 is used for preparation.

8. The use of low-alkali antifreeze silicate cement for plateau areas in concrete according to claim 7, characterized in that: Concrete is calculated by weight and includes: 100 parts of low-alkali frost-resistant silicate cement, 313-354 parts of coarse aggregate, 472-526 parts of fine aggregate, 55-75 parts of fly ash, 28-56 parts of polyester fiber, 1.3-2.6 parts of high-efficiency water reducer and 78-96 parts of water.

9. The use of low-alkali antifreeze silicate cement in concrete for plateau areas according to claim 7, characterized in that: The coarse aggregate is crushed stone or pebbles with a particle size of 5-10 mm, the fine aggregate is river sand or sea sand with a particle size of 0.16-4.5 mm; and the fly ash is Class I fly ash.

10. The use of low-alkali antifreeze silicate cement in concrete for plateau areas according to claim 7, wherein the high-efficiency water reducer is TH-928 polycarboxylic acid-based high-performance water reducer.

Citation Information

Patent Citations

  • Low-alkali cement and preparation process thereof

    CN115259706A

  • Sponge dressing with intelligent antibiosis and infection indication functions and preparation method thereof

    CN115382002A

  • Method for preparing concrete square pile by co-doping nickel slag and fly ash

    CN116768569A